2021
DOI: 10.20944/preprints202106.0708.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interventions and Strategies to Improve Sexual and Reproductive Health Outcomes among Adolescents Living in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis

Abstract: Adolescent’s access to quality Sexual and Reproductive Health and Rights interventions has been a major issue in most of the low- to middle-income countries (LMICs) across the globe. This systematic review aims to identify the relevant community and school-based interventions that can be implemented in -LMICs to promote adolescent’s sexual and reproductive health and rights outcomes. We identified 54 studies and our review findings suggest that Adolescent’s Sexual and Reproductive Health and Rights (ASRHR) edu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Students who did not use the YSRH service were more likely to engage in premarital sexual activity. This finding in line with the studies done in Haramaya High School (35), Eastern Ethiopia (36), Low-and Middle-Income Countries (37), Washington (38), and Sub-Saharan Africa (39). This may be due to the fact that YSRH services like counseling may provide adequate information about the consequences of premarital sex for the users.…”
Section: Discussionsupporting
confidence: 91%
“…Students who did not use the YSRH service were more likely to engage in premarital sexual activity. This finding in line with the studies done in Haramaya High School (35), Eastern Ethiopia (36), Low-and Middle-Income Countries (37), Washington (38), and Sub-Saharan Africa (39). This may be due to the fact that YSRH services like counseling may provide adequate information about the consequences of premarital sex for the users.…”
Section: Discussionsupporting
confidence: 91%
“…Different systematic review study findings showed that school-based peer-led intervention increased contraceptive use after five and 17 months of intervention [ 23 ] and led to a decrease in unwanted pregnancies [ 3 ]. Contraceptive use increased significantly after six months of school-based peer education intervention in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies indicated that educational intervention alone may not increase contraceptive use among adolescents. An intervention focusing on reproductive health services, including comprehensive post-abortion family planning services and financial incentives, produced positive changes in contraceptive utilisation and demand [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations